The influence of Brand personality and customer experience on electronic word of mouth at Maybelline product with brand preference as mediating variable - Shelina Virgarani; Astra Prima Budiarti (Universitas Negeri Padang, 2021)
The purpose of this study was to analyze the influence of Brand personality and customer experience on electronic word of mouth at Maybelline product with brand preference as mediating variable. The type of this research is quantitative research. The population of this study were all users of the maybelline product with the numbers of samples in the study were 180 respondents. This study was analyzed using structural equation modelling (SEM) with Smart PLS3.The result of this study indicate that (1) brand personality has a positive and significant effect on brand preference, (2)Customer experience has a positive and significant effect’s on brand preference, (3) Brand personality has a positiv and significant effect’s on eWOM, (4) Customer experience has positve and significant effect on E eWOM, (5) Brand preference has a positive, and significant effect on electronic word of mouth, (6)Brand personality has a positive and significant effect’s on eWOM through brand preference’s as a mediating variable, (7) Customer experience has a positive and significant effect on Ewom through brand preference as a mediating variable.